Moving to the mines: Motivations of men and women for migration to artisanal and small-scale mining sites in Eastern Democratic Republic of the Congo. (March 2017) - Maclin, Beth J.; Kelly, Jocelyn T.D.; Perks, Rachel; Vinck, Patrick; Pham, Phuong
Abstract: Artisanal and small scale mining (ASM) sites in eastern Democratic Republic of the Congo (DRC) present livelihoods opportunities within an evolving security situation, thus offering the potential for economic and physical security. This paper presents survey data detailing reasons why men and women in eastern DRC migrate to ASM sites, with a specific focus on the extent to which insecurity wrought by the DRC's decades long conflict influences individuals' migration decisions. It draws from research performed under a World Bank-Harvard Humanitarian Initiative research project. Following the literature review on decision-making related to ASM and migration and its applicability to the research context of eastern DRC, the article first presents basic demographics of the 998 men and women surveyed. It then details participants' specific motivations for migration and groups them as push or pull factors. Finally, the article looks at the relationship between migration and the relevant migration and security variables separately before creating a multiple regression model to see how these variables inform migration decisions collectively. Participants largely migrated to ASM sites for the purpose of seeking money and/or employment. Security – specifically the presence of an armed group at one's reception site – also informed migration decision making, yet it did not negate the role of economic factors. This is the first paper the authors know of that examines gender-specific motivations for migration to ASM sites as well as how insecurity influences decisions to migrate to ASM sites. Highlights: ASM is an increasingly attractive livelihoods option in eastern DRC. Participants were driven to ASM sites most often by economic push factors. Economic pull factors were the least cited driver of migration to ASM. Security informed migration decisions, but did not negate economic factors.